"Can I take out my penis?" Navigating Sex and Intimacy in the Workplace: An Empirical Test of Black's Theory of Conflict. Issue 6 (3rd June 2019) - Barlow, Angela
ABSTRACT: As the number of producers, politicians, and celebrities accused of workplace sexual misconduct increases, we understand there is a fine line between flirting at work and behaviors that cause significant conflict. Building on concepts introduced in The Behavior of Law (1976), Donald Black's new theory of conflict, Moral Time (2011), claims generality, explaining when, how, and why some social interactions lead to conflict. This research offers empirical validation of "relational time, " one of the three primary dimensions introduced in Moral Time . Using a factorial survey in which social contexts depicted in vignettes are systematically varied, students' perceptions of offensiveness to sexualized interactions between coworkers were obtained from a sample of students at a large southeastern university ( n  = 1936). Aggregate results show strong support for the relational dimension of Black's theory.